From the screen to the classroom: Transmedia narratives and multimodality in the educational field - Salazar Estrada, Maribel; Giraldo Marín, Sara; Sepúlveda Arango, Mauricio; Álvarez Hernández, Josué (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
The article presents a systematization of experiences that seeks to integrate transmedia narratives in the educational field, with special emphasis on the dissemination and appropriation of concepts about multimodalities by the academic community of the Instituto Universitario de Educación Física y Deporte (IUEFD) of the Universidad de Antioquia. The systematization approach is based on the review of previous research conducted at the IUEFD on the integration of Information and Communication Technologies (ICT) and the perceptions of teachers and students about the combined teaching modalities determined by the University. Likewise, a literature review is carried out on combined educational modalities and the use of transmedia narratives as a pedagogical tool.